Fungal secretomics to probe the biological functions of lytic polysaccharide monooxygenases. (7th August 2017) - Berrin, Jean-Guy; Rosso, Marie-Noëlle; Abou Hachem, Maher
Abstract: Enzymatic degradation of plant biomass is of growing interest for the development of a sustainable bio-based industry. Filamentous fungi, which degrade complex and recalcitrant plant polymers, are proficient secretors of enzymes acting on the lignocellulose composite of plant cell walls in addition to starch, the main carbon storage reservoir. In this review, we focus on the identification of lytic polysaccharide monooxygenases (LPMOs) and their redox partners in fungal secretomes to highlight the biological functions of these remarkable enzyme systems and we discuss future trends related to LPMO-potentiated bioconversion. Graphical abstract: Highlights: Filamentous fungi are proficient secretors of enzymes acting on plant cell walls and starch. Fungal LPMOs are very powerful enzymes involved in oxidative cleavage of polysaccharides. Fungal secretomics enable identification of LPMOs and their redox partners. Fungal secretomics are useful to bring insights into the biological functions of LPMOs.